Evolution and Biogeography of the Genus Heteropoda (Heteropodinae: Sparassidae) Across Southeast Asia - Shakal Khan Korai; Amir Khan Korai; Shengnan Li; Kamil Kabir; Kamran Haider; Muhammad Raheel Tariq; Arif Ali; Xiaoshan Wang (Zoologica Scripta, 2026)
Heteropoda huntsman spiders are large, fast‐moving predators widely distributed across tropical and subtropical regions, where they function as important nocturnal hunters. Despite their ecological prominence, the evolutionary and biogeographic history of the genus remains poorly resolved. Here, we analysed a six‐locus dataset (two mitochondrial and four nuclear genes) to estimate divergence times and reconstruct ancestral ranges within Heteropoda using Bayesian phylogenetic and statistical biogeographic approaches, and we assessed broad climatic suitability using genus‐level ecological niche modelling. Time‐calibrated analyses support the monophyly of Heteropoda and indicate that crown diversification began during the early Oligocene (~30 Ma; 95% HPD: 18–41 Ma). A primary split between Australasian and Asian lineages is inferred near the Oligocene–Miocene transition (~23 Ma; 95% HPD: 14–33 Ma), followed by radiation within Southeast and East Asia. Ancestral‐area reconstructions consistently recover Australasia as a key ancestral component and suggest repeated dispersal and isolation across the Sunda–Wallacea interface under conditions of long‐term tectonic instability. Ecological niche modelling identifies temperature, precipitation, and elevation as major correlates of climatic suitability, consistent with the predominance of Heteropoda in warm and humid environments. Together, these results provide an integrated temporal, spatial, and ecological framework for understanding diversification and present‐day distribution of Heteropoda across Southeast Asia and adjacent regions.

Integrative taxonomy of the featherback fish genus Chitala (Osteoglossomorpha: Notopteridae) in Peninsular Malaysia - Luqman Hakim Ruzman; Jamsari Amirul Firdaus Jamaluddin; Abdullah Halim Muhammad‐Rasul; Tedjo Sukmono; Md. Zain Khaironizam; Sébastien Lavoué (Zoologica Scripta, 2024)
The taxonomy of the freshwater featherback fish genus Chitala (Osteoglossomorpha: Notopteridae) remains unsettled because delimiting and naming Chitala species based solely on morphology led to different hypotheses. In this study, we aim to determine the number and identity of Chitala species present in Peninsular Malaysia by employing an integrative taxonomic approach that combines morphology and two mitochondrial markers: the cytochrome c oxidase subunit I (COI) and cytochrome b genes. A total of 60 specimens of Chitala were collected throughout Peninsular Malaysia. Initially, all specimens were sorted into three distinct categories based on their body marking patterns. A molecular phylogenetic analysis revealed that each of these groups was monophyletic, and an automated species partition method further recognized them as distinct species. These results support the presence of three Chitala species in Peninsular Malaysia, even though a multivariate morphometric analysis failed to fully differentiate each of these three species. Comparison with original species descriptions and genetic data from an additional 70 Chitala specimens from neighbouring regions allowed us to name these species as Chitala lopis , Chitala borneensis , and Chitala ornata . We also showed the presence of two undescribed species in Indonesia.